Effectiveness of Play-Based Learning Approach in Teaching Islamic Values to Early Childhood Children - Labisal Fitri Al Qolbi; Zayin Nafsaka Sajidin (Al-Banat: Journal of Early Childhood Islamic Education, 2025)
This study aims to explore the effectiveness of the play-based learning approach in teaching Islamic values in early childhood. The method was implemented in an early childhood education institution that integrates Islamic values in its curriculum. Through interviews with management, questionnaires to educators, and classroom observations, the study revealed that the play-based approach increased children's engagement and understanding of Islamic values. The results showed that children were more enthusiastic and quickly grasped religious concepts such as prayer, prayer and good manners through play-based activities, such as role-playing and drawing. In addition, this approach also supports children's social and emotional development, such as sharing skills, cooperation and self-control. However, the main challenge found was the limited time for effective implementation of play-based activities. Nonetheless, this study concludes that play-based learning is an effective method in teaching Islamic values, which can enhance the understanding and internalization of these values in young children. Therefore, PAUD education institutions are expected to optimize this approach by providing training for educators and involving parents in the learning process.